(untitled) (Bulletin KNOB, 1989)
With this question attention turns again to the research of possibilities and usefulness to preserve the architecture of the African town Djenné in Mali. Djenné with her rich past certainly is of great socio-historical and architectural importance. Nowadays however the built cultural heritage is posed to fast changes and even is busy to disappear on several vital points. Sahel drynesses, economical recess, a leaving population, changing society and an increasing influence of western consumption-culture can be pointed out as important causes, which unfortunately are not temporary. The priority of an economical reactivation of the region Djenné which could face these problems therefore is logical and does not have to clash at all with the interest of preserving this unique example of real black-African architecture for the future. Next to the affirmation of the own identity a suchlike culture-project namely also would have to benefit the local community. If for example a town-rehabilitation would be executed with local craftsmen, materials and techniques as much as possible a poorer group of the population could be reached directly, which guarantees the preservation of native craftsmanship at the same time. Mali being one of the poorest countries in the world misses the means and organization for such an enterprise, so that nothing can happen without support from outside. During the past decade Djenné has been studied by representatives of many Dutch universities. Researchers from different disciplines like archeology, architecture, civil technique, cultural anthropology and social geography made researches there mostly in co-operation with the Malinesian Institut des Sciences Humaines. This knowledge can form an excellent contribution for the design of Djenné’s rehabilitationplan.